Trapped in the care burden: occupational downward mobility of Italian couples after childbirth - Teresa Barbieri; Michele Bavaro; Valeria Cirillo (Global Labor Organization (GLO), 2024)
How does childbirth impact the career paths of men and women within the same household? To what extent does the unpaid care work related to this event contribute to the downward mobility experienced by women in a highly flexible labour market like Italy? Drawing on feminist and labour market studies, this article examines how caregiving responsibilities, particularly childcare, influence downward employment transitions for men and women in couples, specifically from full-time to part-time, from higher-paid to lower-paid jobs, and from employment to unemployment. The study also employs latent class analysis to map out variations in within-household inequality experienced after childbirth among couples. To achieve this, we utilize a unique survey-administrative linked dataset. The findings highlight significant penalties faced by women, not only immediately after childbirth but persisting for up to three years afterwards. Moreover, the latent class analysis reveals a small proportion of pro-female households compared to egalitarian and pro-male classes.
Keywords: J13; J16; E24; 330; Gender pay gaps; occupational downward mobility; gender inequalities; motherhood penalty; micro-econometric analyses